Enhancing electrical discharge machining performance through nano H₂/O₂ bubble integration: A sustainable and optimized approach - Chia-Lung Kuo; Chin-Ta Chen; Chao-Ching Ho (Micro and Nano Engineering, 2025)
This study explores the integration of nano H₂/O₂ bubble liquid into Electrical Discharge Machining (EDM) and its impact on machining efficiency, precision, and sustainability. Experimental results demonstrate that the use of nano H2/O2 bubbles significantly enhances discharge dispersion, improves fluid flow for chip removal, and increases overall machining energy. For SUS316, machining time was reduced by up to 25 %, and for Ti6Al4V, by up to 31 %, when using a ϕ0.3 mm electrode. Additionally, electrode consumption decreased by up to 36 %, leading to improved cost-efficiency and reduced wear. The findings highlight the potential of nano H2/O2 bubble liquid in boosting EDM performance, offering a practical and environmentally sustainable solution for industrial applications by optimizing machining time, electrode consumption, and overall energy efficiency.